The Relation between Plasma Tissue Factor and Oxidized LDL Levels in Acute Coronary Syndromes - ALTURFAN, EBRU IŞIK (KARGER, 2007)
Aim: Tissue factor (TF) is a low-molecular-weight glycoprotein responsible for the initiation of the coagulation cascade. The relation between oxidized low-density lipoprotein (OxLDL), that has been shown to be involved in atherogenesis, and TF has not been evaluated before in circulating plasma. The aim of this study was to determine plasma levels of TF and Ox-LDL in acute coronary syndrome (ACS) and stable coronary artery disease (SCAD). Methods: The study group consisted of 41 patients with ACS and 26 patients with SCAD. Among the ACS patients, 12 were diagnosed with unstable angina pectoris (UAP) and 29 were diagnosed with acute myocardial infarction (AMI). The control group consisted of 30 healthy volunteers. TF and Ox-LDL levels were evaluated by ELISA kits. Results: Ox-LDL levels were significantly higher in UAP and AMI patients compared with the control (p < 0.001) and SCAD (p < 0.01 and p < 0.001, respectively) groups. TF levels were significantly higher in the UAP, AMI and SCAD groups compared with the control group (p < 0.001, p < 0.001 and p < 0.01, respectively). In the AMI group a significant increase was observed in TF levels when compared with the SCAD group (p < 0.01). Plasma Ox-LDL levels were significantly and positively correlated with TF levels in the UAP and AMI groups (p < 0.05, r = 702, and p < 0.0001, r = 0.679, respectively). Conclusion: The potential link between OxLDL and TF in circulating blood in ACS may strengthen the evidence supporting a relationship between oxidant stress, lipids and thrombosis and consequently may contribute to understanding the mechanism through which Ox-LDL and TF may mediate the pathogenesis of CAD. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Acute coronary syndromes; Oxidized low-density; lipoprotein; Plasma; Tissue factor